Sodium ferric pyrophosphate positive electrode material as well as preparation method and application thereof

By introducing Fe vacancies and high entropy doped ions into the sodium ferric pyrophosphate positive electrode material and using the dual carbon auxiliary sol gel method, the material's shortcomings in magnification capacity and cyclic stability are solved, and the effect of high purity phase structure and high power density is achieved.

CN119683595AActive Publication Date: 2025-03-25CENT SOUTH UNIV

Patent Information

Application Number
CN202411858370.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing sodium ferric pyrophosphate positive electrode materials have shortcomings in electrochemical properties, especially in terms of ratio capacity and cycle stability, and it is difficult to accurately introduce anionic groups during the synthesis process to lead to the existence of impurity phases.

Method used

By introducing Fe vacancies and a variety of high entropy doped ions, the dual-carbon auxiliary sol gel method is used to achieve high-purity phase structure and carbon coating of the material, and improve the electronic conductivity and structural stability of the material.

Benefits of technology

It significantly improves the intrinsic conductivity and structural stability of the sodium ferric pyrophosphate positive electrode material, achieves high power density and ultra-long cycle life, and ensures the phase purity and low cost characteristics of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683595A_ABST
    Figure CN119683595A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ferric pyrophosphate positive electrode material as well as a preparation method and application thereof. The chemical formula of the sodium ferric pyrophosphate positive electrode material is Na4Fe3-x-y-xHEy (PO4) 2P2O7, wherein:-is a Fe vacancy; hE is a doping element and comprises at least five of Ni, Mg, Co, Mn, Cu, Zn, Cd, Al and Cr, and the mole of each doping element is equal; 0, 0.08 lt; x is greater than or equal to 0.2 and less than or equal to 0.3. The Fe vacancy and high-entropy doping coordinated regulation multi-defect phosphoric acid ferric sodium pyrophosphate positive electrode material provided by the invention not only has a high-purity phase structure, but also remarkably improves the ion / electron conductivity and structural stability of the material by Fe vacancy and high-entropy doping, and can realize more than 15000 times of stable circulation under high rate. The invention further provides a double-carbon-assisted sol-gel synthesis method which is simple, easy to operate and low in cost, and in-situ carbon coating and morphology regulation and control can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion battery positive electrode materials, and in particular relates to a sodium iron phosphate pyrophosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] Efficient energy storage technology is a prerequisite for the utilization of sustainable energy. In recent decades, the emergence of lithium-ion batteries has greatly promoted the development of portable electronic devices and electric vehicles, but there is still a large gap between supply and demand. In particular, limited lithium resources have largely restricted the development of large-scale energy storage. In contrast, sodium-ion batteries have become an important supplement to large-scale energy storage due to their advantages such as high abundance, wide distribution and low cost of sodium resources. However, the large radius and heavy atomic mass of sodium ions easily lead to structural failure of electrodes and slow electrochemical reaction kinetics, accompanied by huge volume changes during charging and discharging, which have become obstacles to the commercial development of sodium-ion batteries. It is well known that the cathode plays a key role in determining the cost and electrochemical performance of the battery system, so it is necessary to vigorously explore advanced cathodes with high operating voltage, high specific capacity and high cycle stability. Among them, polyanion cathode materials have attracted widespread attention due to their excellent structural stability, long cycle life, high safety and abundant resources.

[0003] As the most representative iron-based phosphate cathode material, sodium iron pyrophosphate (Na4Fe3(PO4)2P2O7) has a high capacity of 129 mAh g -1 The theoretical capacity and voltage platform close to 3.1V. Thanks to its three-dimensional open Na + Diffusion channel, Na4Fe3(PO4)2P2O7 exhibits small volume change and strong structural stability during the deintercalation process. In addition, compared with toxic vanadium-based and structurally unstable manganese-based phosphate compounds, the Na4Fe3(PO4)2P2O7 cathode has the dual advantages of low cost and high performance, and has good commercial prospects, especially in high power density applications. However, due to its poor electronic conductivity and slow sodium ion diffusion behavior, the electrochemical performance of Na4Fe3(PO4)2P2O7 is subject to certain limitations, especially in terms of rate capability and cycle stability. In order to solve these problems, various strategies are often adopted, such as nano-sizing, carbon coating (e.g., carbon black, graphene, carbon nanotubes), and element doping (e.g., Mn 2+ 、Co 2+ Mg 2+ , Cu 2+) and other optimization methods. In addition, since the two anionic groups cannot be accurately introduced during the synthesis process, an indelible impurity phase has always existed in the synthesis of Na4Fe3(PO4)2P2O7. In particular, the current research on the synthesis methods of high-performance Na4Fe3(PO4)2P2O7 materials mainly focuses on ball milling and spray drying. The development of a simple, efficient, low-cost, and consistent material synthesis method also has important practical value.

[0004] In view of this, how to effectively improve the intrinsic conductivity and structural stability of sodium iron pyrophosphate positive electrode materials through a simple synthesis method, improve the material's tolerance under high current density and long-cycle stability, while ensuring the phase purity of the material, is a technical problem that needs to be solved urgently. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a high-performance, low-cost sodium iron pyrophosphate positive electrode material and a preparation method and application thereof.

[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0007] A sodium iron phosphate pyrophosphate positive electrode material, the chemical formula of which is Na4Fe 3-x-y □ x HE y (PO4)2P2O7; wherein: □ is an Fe vacancy; HE is a doping element, including at least 5 of Ni, Mg, Co, Mn, Cu, Zn, Cd, Al, and Cr, and each doping element is equimolar; 0.08 <x≤0.1,0.2≤y≤0.3。

[0008] As a further improvement, the surface of the positive electrode material is coated with a carbon layer, wherein the carbon content accounts for 5-12wt% of the positive electrode material.

[0009] The present invention also provides a method for preparing the sodium iron phosphate pyrophosphate positive electrode material, comprising the following steps:

[0010] Step S1, dissolving carbon source A and carbon source B in water, and performing ultrasonic treatment to obtain a carbon source solution;

[0011] Step S2, adding the iron source and the metal doping element source into the solution of step S1 according to the stoichiometric ratio, heating and stirring;

[0012] Step S3, adding the sodium source and the phosphorus source into the solution of step S2 according to the stoichiometric ratio, heating and stirring, and then evaporating to obtain a gel;

[0013] Step S4, drying the gel of step S3, grinding it into powder, and then tableting it to obtain a sheet-like precursor;

[0014] Step S5, calcining the sheet precursor obtained in step S4 under an inert atmosphere, and then cooling and grinding to obtain the sodium iron phosphate pyrophosphate positive electrode material.

[0015] As a further improvement, the carbon source A in S1 is one or more of polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, sodium alginate, and polyacrylamide; the carbon source B is one or more of sucrose, glucose, citric acid, ascorbic acid, oxalic acid, and oxalic acid.

[0016] As a further improvement, the concentration of the carbon source A in the carbon source solution is controlled at 12-18 mg / mL, and the concentration of the carbon source B in the carbon source solution is controlled at 65-75 mg / mL.

[0017] As a further improvement, the carbon source A and the carbon source B are polyvinyl pyrrolidone and citric acid respectively.

[0018] As a further improvement, the heating and stirring temperature in S2 and S3 is 60-90°C; the tableting pressure in S4 is 20-40MPa.

[0019] As a further improvement, the calcination temperature in S5 is 550-650°C and the holding time is 8-12h.

[0020] The present invention also provides a sodium ion battery positive electrode plate, which comprises the sodium iron phosphate pyrophosphate positive electrode material, or the sodium iron phosphate pyrophosphate positive electrode material prepared by the method.

[0021] The present invention also provides a sodium ion battery, which comprises the sodium ion battery positive electrode plate.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The applicant's research found that in order to improve phase purity, both the Fe vacancy control strategy and the high entropy doping strategy have certain limitations. The introduction of Fe vacancies reduces the stability of the material, and high entropy doping easily causes irreversible capacity loss.

[0024] To this end, the present invention provides a high-performance, low-cost multi-defect sodium iron phosphate pyrophosphate positive electrode material with coordinated regulation of high entropy doping and Fe vacancies, which can achieve significant improvement in its intrinsic conductivity and structural stability, has high-purity phase structure and high power density characteristics, and can achieve ultra-stable cycling of sodium ion batteries at high current density. Among them, the introduction of Fe vacancies can effectively inhibit the formation of NaFePO4 impurity phases, but excessive Fe vacancies can easily lead to structural collapse and reduce material stability. On this basis, the adverse lattice distortion caused by Fe vacancies is further stabilized by adding a variety of high-entropy doping ions, thereby improving the cyclic stability of the material. On the one hand, the introduction of Fe vacancies not only ensures phase purity, but also further improves the entropy value of sodium iron phosphate pyrophosphate; on the other hand, the appropriate concentration of high entropy doping not only provides a flexible local environment, but also stabilizes the structural instability caused by Fe vacancies.

[0025] The sodium iron phosphate pyrophosphate positive electrode material provided by the present invention has good reversibility and small volume strain during the charge and discharge process. In the in-situ XRD test, the maximum volume change of the electrode material is only 3.8%, and the lattice parameters can be restored to the initial state after the test. It has good high-power characteristics and exhibits an ultra-long cycle life (15,000 cycles at 5A g -1 conditions) and excellent rate performance (61.1 mAh g -1 At 10A g -1 conditions), indicating that it has good application prospects.

[0026] Compared with the traditional sol-gel method, the present invention adopts a dual-carbon assisted sol-gel method, which achieves uniform in-situ carbon coating and microsphere morphology regulation and uniform distribution of doping elements by regulating the concentration of two carbon sources with different pyrolysis characteristics. At the same time, an interwoven carbon matrix network is constructed, which improves the electronic conductivity and shortens the Na + Diffusion path, increasing the Na + The diffusion rate shows smaller volume change and better structural stability during the deintercalation process, and has strong practical value. The process of the invention is simple and easy to operate, low in cost, can be mass-produced, and has good material consistency and strong stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1This is a macroscopic SEM image of the sodium ion battery positive electrode material prepared in Example 1 of the present invention;

[0029] Figure 2 This is a local SEM image of the sodium ion battery positive electrode material prepared in Example 1 of the present invention;

[0030] Figure 3 This is a macroscopic SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 0 of the present invention;

[0031] Figure 4 This is a local SEM image of the sodium ion battery positive electrode material prepared in Comparative Example 0 of the present invention;

[0032] Figure 5 XRD spectra of the sodium ion battery positive electrode materials prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 of the present invention;

[0033] Figure 6 The locally enlarged XRD spectra of the sodium ion battery positive electrode materials prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 of the present invention;

[0034] Figure 7 The sodium ion battery positive electrode materials prepared in Comparative Examples 1, 2, 3 and Example 1 of the present invention are 10 mA g -1 Initial charge and discharge curves at current density;

[0035] Figure 8 The figure is a rate performance diagram of the sodium ion battery positive electrode material prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 of the present invention;

[0036] Fig. 9 The sodium ion battery positive electrode material prepared in Example 1 of the present invention is 5A g -1 Long cycle electrochemical performance diagram under current density;

[0037] Fig.10 The sodium ion battery positive electrode material obtained in Comparative Examples 1, 2 and 3 of the present invention is 5A g -1 Long cycle electrochemical performance diagram under current density;

[0038] Fig.11 This is the in-situ XRD pattern of the sodium ion battery positive electrode material prepared in Example 1 of the present invention corresponding to the initial two cycles of charge and discharge. DETAILED DESCRIPTION

[0039] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0040] Unless otherwise defined, all technical terms used hereinafter have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing specific embodiments only and are not intended to limit the scope of the present invention.

[0041] Unless otherwise specifically stated, various raw materials, reagents, instruments, and equipment used in the present invention can be obtained through the market or prepared by existing methods.

[0042] The sodium iron pyrophosphate phosphate cathode material of the present invention has the chemical formula Na4Fe 3-x-y □ x HE y (PO4)2P2O7; wherein:

[0043] 0.08 < x ≤ 0.1, 0.2 ≤ y ≤ 0.3. In some embodiments, the value of x can be 0.085, 0.09, 0.095 or 0.1, or other values within the range of 0.08 < x ≤ 0.1; the value of y can be 0.2, 0.25 or 0.3, or other values within the range of 0.2 ≤ y ≤ 0.3.

[0044] HE is a doping element, including at least 5 of Ni, Mg, Co, Mn, Cu, Zn, Cd, Al, Cr, and each doping element is in equimolar amounts. In some embodiments, the types of doping elements can be any combination of five or six of Ni, Mg, Co, Mn, Cu, Zn, Cd, Al, Cr.

[0045] □ is an Fe vacancy, which refers to adding less than the stoichiometric ratio of Fe source, resulting in some Fe sites being vacant. The Fe vacancy is introduced by controlling the Fe content in the material system. The molar concentration of the Fe vacancy accounts for 2.7% - 3.3% of the Fe sites, that is, 96.7 - 97.3% of the Fe sites are occupied by Fe and doping elements, and the rest are Fe vacancies. The present invention has obtained a high-purity Na4Fe3(PO4)2P2O7 single-phase structure through the synergistic regulation of Fe vacancies and high-entropy doping. A variety of metal elements (i.e., doping element HE) on the Fe sites are incorporated into the lattice in equimolar ratios to achieve the maximum entropy value. The introduction of Fe vacancies can inhibit the formation of the impurity phase NaFePO4 and further increase the entropy value of the system.

[0046] The matrix structure of the sodium iron pyrophosphate phosphate cathode material of the present invention is a Na4Fe3(PO4)2P2O7 single-phase structure with the space group Pn21a. All metal doping elements are incorporated into the Fe sites in equimolar amounts, and the doping elements all have 2+ similar radii and good chemical compatibility with Fe, and no charge transfer occurs between elements.

[0047] The present invention achieves the regulation of configuration entropy by introducing equimolar metal doping elements, further alleviates the adverse lattice distortion caused by Fe vacancies through the entropy stabilization effect, and improves the structural stability of the material.

[0048] The Fe vacancies, Fe elements and various metal doping elements in the material have good chemical compatibility and can occupy the Fe sites well, giving the phosphate pyrophosphate material a flexible and changeable local environment, effectively alleviating the Na + Volumetric strain during the embedding and de-embedding process.

[0049] Therefore, the coordinated regulation of Fe vacancies and high entropy doping in the present invention can effectively improve the ionic / electronic conductivity of the material while ensuring the pure phase structure and cyclic stability of the material. The two strategies have achieved the effect of 1+1>2.

[0050] The present invention successfully synthesizes a multi-defective sodium iron phosphate pyrophosphate positive electrode material with a perfect high-purity phase structure by introducing 2.7%-3.3% Fe vacancies (calculated based on the Fe content).

[0051] The multi-defect sodium iron phosphate pyrophosphate positive electrode material of the present invention not only has a high-purity phase structure, but also the Fe vacancies and high entropy doping significantly improve the ion / electronic conductivity and structural stability of the material, thereby achieving more than 15,000 stable cycles at a high rate.

[0052] In some embodiments, the positive electrode material of the present invention is a spherical particle of sodium iron pyrophosphate coated with a uniform thin carbon layer on the surface, and the carbon content is controlled to be 5-12 wt % of the positive electrode material.

[0053] In some specific embodiments of the present invention, the method for preparing the sodium iron phosphate pyrophosphate positive electrode material comprises the following steps:

[0054] Step S1, dissolving carbon source A and carbon source B in water, and performing ultrasonic treatment to obtain a uniformly dispersed transparent carbon source solution.

[0055] In some embodiments, carbon source A and carbon source B with good water solubility are selected. The carbon source A is one of polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, sodium alginate, and polyacrylamide; the carbon source B is one of sucrose, glucose, citric acid, ascorbic acid, oxalic acid, and oxalic acid. Carbon source A and carbon source B preferably use polyvinyl pyrrolidone (PVP) and citric acid. The concentration of the carbon source A is controlled at 12-18 mg / mL (preferably 14-16 mg / mL), and the concentration of the carbon source B is controlled at 65-75 mg / mL (preferably 67-73 mg / mL).

[0056] The present invention achieves uniform carbon coating and microsphere morphology regulation (different from the irregular nanoparticles synthesized by traditional sol-gel method) by regulating the concentration of two carbon sources A and B with different pyrolysis characteristics, constructs a uniform thin carbon layer in situ on the surface of the material, and constructs an interwoven carbon matrix network to form a unique microsphere embedded in a continuous carbon matrix morphology, improves electronic conductivity, and shortens the Na + Diffusion path, increasing the Na + Diffusion rate.

[0057] In some embodiments, the ultrasonic treatment time is 0.3-0.6 h, specifically 0.3, 0.4, 0.5 or 0.6 h, or other values ​​within this range.

[0058] Step S2: adding the iron source and the metal doping element source (HE) into the solution of step S1 according to the stoichiometric ratio, and heating and stirring the solution sufficiently.

[0059] In some embodiments, the iron source is one or more of ferrous acetate, ferrous sulfate, ferric phosphate, ferric nitrate, ferric citrate, and ferric acetylacetonate; the metal doping element source is one or more of the corresponding metal sulfates, nitrates, and acetates.

[0060] In some embodiments, the heating stirring temperature is 60-90°C, the rotation speed is 300-500 rpm, and the treatment time is 2-5 hours. The stirring temperature can be 60°C, 70°C, 80°C or 90°C, or other values ​​within the range; the rotation speed can be 300, 350, 400, 450 or 500 rpm, or other values ​​within the range; the treatment time can be 2, 3, 4 or 5 hours, or other values ​​within the range.

[0061] Step S3, adding the sodium source and the phosphorus source into the solution of step S2 according to the stoichiometric ratio, heating and stirring evenly, and then evaporating to obtain a light yellow gel.

[0062] In some embodiments, the sodium source is one or more of sodium acetate, sodium dihydrogen phosphate, sodium nitrate, and sodium pyrophosphate; the phosphorus source is one or more of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and sodium pyrophosphate.

[0063] In some embodiments, the heating stirring temperature is 60-90°C, the rotation speed is 300-500 rpm, and the treatment time is 2-4 hours. The stirring temperature can be 60°C, 70°C, 80°C or 90°C, or other values ​​within the range; the rotation speed can be 300, 350, 400, 450 or 500 rpm, or other values ​​within the range; the treatment time can be 2, 3, 4 hours, or other values ​​within the range.

[0064] Step S4, vacuum drying the gel of step S3, grinding it into powder, and tableting it to obtain a sheet precursor.

[0065] In some embodiments, the vacuum drying temperature is 80-110°C, the drying time is 24-30h; the diameter of the tablet is 1-2cm, and the pressure is 20-40MPa. The drying temperature can be 80°C, 90°C, 100°C or 110°C, or other values ​​within the range; the drying time can be 24, 26, 28 or 30h, or other values ​​within the range. The tablet diameter can be 1, 1.2, 1.5, 1.8 or 2cm, or other values ​​within the range; the pressure value can be 20, 30, 40MPa, or other values ​​within the range.

[0066] Direct sintering of powders is prone to unevenness. The use of tableting can effectively improve the crystallinity of the material, and the resulting material has better uniformity and consistency.

[0067] Step S5, calcining the flaky precursor obtained in step S4 at high temperature under an inert atmosphere, then cooling to room temperature, and grinding to obtain the sodium iron phosphate pyrophosphate positive electrode material with coordinated regulation of high entropy doping and Fe vacancies of the present invention.

[0068] In some embodiments, the inert gas is one of argon, nitrogen, an argon-hydrogen mixture, or a nitrogen-hydrogen mixture.

[0069] In some embodiments, the calcination temperature is 550-650°C, the holding time is 8-12h, and the heating rate is 2-5°C / min. The calcination temperature can be 550, 600, 650°C, or other values ​​within the range; the holding time is 8, 9, 10, 11 or 12h, or other values ​​within the range; the heating rate can be 2, 3, 4 or 5°C / min -1 , or other values ​​within this range.

[0070] In some specific embodiments of the present invention, the positive electrode plate of a sodium ion battery is prepared from the sodium iron phosphate pyrophosphate positive electrode material of the present invention, a conductive additive, a binder and a solvent.

[0071] In some embodiments, the conductive additive is one or more of acetylene black, Super P, and Ketjen black; the binder is polyvinylidene fluoride, and the solvent is N-methyl-2-pyrrolidone.

[0072] In some specific embodiments of the present invention, a sodium ion battery comprises the positive electrode sheet of the sodium ion battery, and the sodium ion battery comprises a positive electrode shell, the positive electrode sheet of the sodium ion battery, a diaphragm, an organic electrolyte, metallic sodium, a gasket, a spring, and a negative electrode shell.

[0073] The present invention provides a simple, easy-to-operate, low-cost dual-carbon-assisted sol-gel synthesis method, which can realize in-situ carbon coating and morphology control, and achieve uniform distribution of doping elements. It is an efficient method for preparing multi-defect sodium iron phosphate pyrophosphate positive electrode materials with good consistency.

[0074] The positive electrode material and the preparation method thereof of the present invention are described in detail below through specific examples.

[0075] Comparative Example 0: Preparation of Na4Fe3(PO4)2P2O7 sodium ion battery positive electrode material with low carbon source concentration

[0076] This comparative example adopts the sol-gel method to prepare the Na4Fe3(PO4)2P2O7 positive electrode material, and the preparation method comprises the following steps:

[0077] (1) 0.5 g polyvinylpyrrolidone (PVP) and 4.7 g citric acid (C6H8O7) were dissolved in deionized water (concentrations were 7.143 mg / ml and 67.143 mg / ml, respectively), and ultrasonically treated for 30 min. Then, 15 mmol ferric nitrate nonahydrate (Fe(NO3)3·9H2O) was added thereto, and heated and stirred at 80°C, 400 rpm for 5 h. Then, 20 mmol sodium dihydrogen phosphate dihydrate (NaH2PO4) was added thereto, and heated and stirred at 80°C, 500 rpm for 3 h. Then, the mixture was heated and evaporated at 90°C, 500 rpm to obtain a yellow gel precursor.

[0078] (2) The precursor obtained in step (1) was placed in a vacuum oven and dried at 100°C for 25 hours. The dried material was ground and pressed into a sheet material with a diameter of 1 cm at a pressure of 30 MPa. The obtained material sheet was heated to 600°C at a heating rate of 2°C / min in a hydrogen-argon mixed gas, kept at this temperature for 12 hours, and naturally cooled to room temperature to obtain a blank sample Na4Fe3(PO4)2P2O7 material with low carbon source concentration in situ carbon coating.

[0079] Comparative Example 1: Preparation of blank sample Na4Fe3(PO4)2P2O7 sodium ion battery positive electrode material

[0080] This comparative example adopts the sol-gel method to prepare the Na4Fe3(PO4)2P2O7 positive electrode material, and the preparation method comprises the following steps:

[0081] (1) Dissolve 1 g of polyvinylpyrrolidone (PVP) and 4.7 g of citric acid (C6H8O7) in deionized water (concentrations were 14.286 mg / ml and 67.143 mg / ml, respectively), ultrasonically treat for 30 min, then add 15 mmol of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), heat and stir at 80°C, 400 rpm for 5 h, then add 20 mmol of sodium dihydrogen phosphate dihydrate (NaH2PO4), heat and stir at 80°C, 500 rpm for 3 h, and then heat and evaporate at 90°C, 500 rpm to obtain a yellow gel precursor.

[0082] (2) The precursor obtained in step (1) was placed in a vacuum oven and dried at 100°C for 25 hours. The dried material was ground and pressed into a sheet material with a diameter of 1 cm at a pressure of 30 MPa. The obtained material sheet was heated to 600°C at a heating rate of 2°C / min in a hydrogen-argon mixed gas, kept at this temperature for 12 hours, and naturally cooled to room temperature to obtain an in-situ carbon-coated blank sample Na4Fe3(PO4)2P2O7 material.

[0083] Comparative Example 2: Preparation of Fe vacancy-modified Na4Fe 2.9 □ 0.1 (PO4)2P2O7 Cathode Materials for Sodium Ion Batteries

[0084] This comparative example was prepared by sol-gel method, Na4Fe 2.9 □ 0.1 The preparation method of (PO4)2P2O7 positive electrode material comprises the following steps:

[0085] (1) Dissolve 1 g of polyvinylpyrrolidone (PVP) and 4.7 g of citric acid (C6H8O7) in deionized water (concentrations were 14.286 mg / ml and 67.143 mg / ml, respectively), ultrasonically treat for 30 min, then add 14.5 mmol of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), heat and stir at 80°C, 400 rpm for 5 h, then add 20 mmol of sodium dihydrogen phosphate dihydrate (NaH2PO4), heat and stir at 80°C, 500 rpm for 3 h, and then heat and evaporate at 90°C, 500 rpm to obtain a yellow gel precursor.

[0086] (2) The precursor obtained in step (1) was placed in a vacuum oven and dried at 100°C for 25 hours. The dried material was ground and pressed into a sheet material with a diameter of 1 cm at a pressure of 30 MPa. The obtained material sheet was heated to 600°C at a heating rate of 2°C / min in a hydrogen-argon mixed gas, kept at this temperature for 12 hours, and naturally cooled to room temperature to obtain in-situ carbon-coated Fe vacancy-regulated Na4Fe2.9 □ 0.1 (PO4)2P2O7 material.

[0087] Comparative Example 3: Preparation of high entropy doped Na4Fe 2.7 (Ni, Co, Mn, Cu, Zn, Mg) 0.05 (PO4)2P2O7 sodium ion battery positive electrode material (Fe vacancy is 0)

[0088] This comparative example was prepared by sol-gel method, Na4Fe 2.7 (Ni, Co, Mn, Cu, Zn, Mg) 0.05 The preparation method of (PO4)2P2O7 positive electrode material comprises the following steps:

[0089] (1) 1 g polyvinylpyrrolidone (PVP) and 4.7 g citric acid (C6H8O7) were dissolved in deionized water (concentrations were 14.286 mg / ml and 67.143 mg / ml, respectively), and ultrasonically treated for 30 min. Then, 13.5 mmol ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 0.25 mmol nickel acetate tetrahydrate (NiC4H6O4·4H2O), 0.25 mmol cobalt acetate tetrahydrate (CoC4H6O4·4H2O), and 0.25 mmol manganese acetate tetrahydrate (MnC4H6O4 ·4H2O), 0.25mmol copper acetate monohydrate (C4H6CuO4·H2O), 0.25mmol zinc acetate dihydrate (C4H6O4Zn·2H2O), and 0.25mmol magnesium acetate tetrahydrate (C4H6MgO4·4H2O) were added thereto, heated and stirred at 80°C and 400rpm for 5h, and then 20mmol sodium dihydrogen phosphate dihydrate (NaH2PO4) was added, heated and stirred at 80°C and 500rpm for 3h, and then heated and evaporated at 90°C and 500rpm to obtain a yellow gel precursor.

[0090] (2) The precursor obtained in step (1) was placed in a vacuum oven and dried at 100°C for 25 hours. The dried material was ground and pressed into a sheet material with a diameter of 1 cm at a pressure of 30 MPa. The obtained material sheet was heated to 600°C at a heating rate of 2°C / min in a hydrogen-argon mixed gas, kept at this temperature for 12 hours, and naturally cooled to room temperature to obtain in-situ carbon-coated high-entropy doped Na4Fe 2.7 (Ni, Co, Mn, Cu, Zn, Mg) 0.05 (PO4)2P2O7 material.

[0091] Example 1: Preparation of Na4Fe synergistically regulated by Fe vacancy and high entropy doping 2.6 □ 0.1(Ni, Co, Mn, Cu, Zn, Mg) 0.05 (PO4)2P2O7 sodium ion battery positive electrode material (x=0.1;y=0.3)

[0092] This embodiment adopts sol-gel method to prepare Na4Fe 2.6 □ 0.1 (Ni, Co, Mn, Cu, Zn, Mg) 0.05 The preparation method of (PO4)2P2O7 positive electrode material comprises the following steps:

[0093] (1) 1 g of polyvinyl pyrrolidone (PVP) and 4.7 g of citric acid (C6H8O7) were dissolved in deionized water (concentrations were 14.286 mg / ml and 67.143 mg / ml, respectively), and ultrasonically treated for 30 min. Then, 13 mmol of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 0.25 mmol of nickel acetate tetrahydrate (NiC4H6O4·4H2O), 0.25 mmol of cobalt acetate tetrahydrate (CoC4H6O4·4H2O), and 0.25 mmol of manganese acetate tetrahydrate (MnC4H6O4· 4H2O), 0.25mmol copper acetate monohydrate (C4H6CuO4·H2O), 0.25mmol zinc acetate dihydrate (C4H6O4Zn·2H2O), and 0.25mmol magnesium acetate tetrahydrate (C4H6MgO4·4H2O) were added thereto, heated and stirred at 80°C and 400rpm for 5h, and then 20mmol sodium dihydrogen phosphate dihydrate (NaH2PO4) was added, heated and stirred at 80°C and 500rpm for 3h, and then heated and evaporated at 90°C and 500rpm to obtain a yellow gel precursor.

[0094] (2) The precursor obtained in step (1) was placed in a vacuum oven and dried at 100°C for 25 hours. The dried material was ground and pressed into a sheet material with a diameter of 1 cm at a pressure of 30 MPa. The obtained material sheet was heated to 600°C at a heating rate of 2°C / min in a hydrogen-argon mixed gas, kept at this temperature for 12 hours, and naturally cooled to room temperature to obtain Na4Fe2O3 synergistically regulated by in-situ carbon-coated Fe vacancies and high entropy doping. 2.6 □ 0.1 (Ni, Co, Mn, Cu, Zn, Mg) 0.05 (PO4)2P2O7 material.

[0095] Example 2: Preparation of Na4Fe synergistically regulated by Fe vacancy and high entropy doping 2.6 □ 0.1 (Ni, Co, Mn, Cu, Al, Mg) 0.05(PO4)2P2O7 sodium ion battery positive electrode material (x=0.1;y=0.3)

[0096] This embodiment adopts sol-gel method to prepare Na4Fe 2.6 □ 0.1 (Ni, Co, Mn, Cu, Al, Mg) 0.05 The preparation method of (PO4)2P2O7 positive electrode material comprises the following steps:

[0097] (1) 1 g of polyvinyl pyrrolidone (PVP) and 4.7 g of citric acid (C6H8O7) were dissolved in deionized water (concentrations were 14.286 mg / ml and 67.143 mg / ml, respectively), and ultrasonically treated for 30 min. Then, 13 mmol of ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 0.25 mmol of nickel acetate tetrahydrate (NiC4H6O4·4H2O), 0.25 mmol of cobalt acetate tetrahydrate (CoC4H6O4·4H2O), and 0.25 mmol of manganese acetate tetrahydrate (MnC4H6O4· 4H2O), 0.25mmol copper acetate monohydrate (C4H6CuO4·H2O), 0.25mmol aluminum nitrate nonahydrate (Al(NO3)3·9H2O), and 0.25mmol magnesium acetate tetrahydrate (C4H6MgO4·4H2O) were added thereto, heated and stirred at 80°C and 400rpm for 5h, and then 20mmol sodium dihydrogen phosphate dihydrate (NaH2PO4) was added, heated and stirred at 80°C and 500rpm for 3h, and then heated and evaporated at 90°C and 500rpm to obtain a yellow gel precursor.

[0098] (2) The precursor obtained in step (1) was placed in a vacuum oven and dried at 100°C for 25 hours. The dried material was ground and pressed into a sheet material with a diameter of 1 cm at a pressure of 30 MPa. The obtained material sheet was heated to 600°C at a heating rate of 2°C / min in a hydrogen-argon mixed gas, kept at this temperature for 12 hours, and naturally cooled to room temperature to obtain Na4Fe2O3 synergistically regulated by in-situ carbon-coated Fe vacancies and high entropy doping. 2.6 □ 0.1 (Ni, Co, Mn, Cu, Al, Mg) 0.05 (PO4)2P2O7 material.

[0099] Example 3: Preparation of Na4Fe synergistically regulated by Fe vacancy and high entropy doping 2.6 □ 0.1 (Ni,Co,Mn,Cu,Mg) 0.06 (PO4)2P2O7 sodium ion battery positive electrode material (x=0.1;y=0.3)

[0100] This embodiment adopts sol-gel method to prepare Na4Fe 2.6 □ 0.1 (Ni,Co,Mn,Cu,Mg) 0.06 The preparation method of (PO4)2P2O7 positive electrode material comprises the following steps:

[0101] (1) 1 g polyvinylpyrrolidone (PVP) and 4.7 g citric acid (C6H8O7) were dissolved in deionized water (concentrations were 14.286 mg / ml and 67.143 mg / ml, respectively), and ultrasonically treated for 30 min. Then, 13 mmol ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 0.3 mmol nickel acetate tetrahydrate (NiC4H6O4·4H2O), 0.3 mmol cobalt acetate tetrahydrate (CoC4H6O4·4H2O), and 0.3 mmol tetrahydrate were added. Manganese acetate (MnC4H6O4·4H2O), 0.3mmol copper acetate monohydrate (C4H6CuO4·H2O), and 0.3mmol magnesium acetate tetrahydrate (C4H6MgO4·4H2O) are added thereto, heated and stirred at 80°C and 400rpm for 5h, and then 20mmol sodium dihydrogen phosphate dihydrate (NaH2PO4) is added, heated and stirred at 80°C and 500rpm for 3h, and then heated and evaporated at 90°C and 500rpm to obtain a yellow gel precursor.

[0102] (2) The precursor obtained in step (1) was placed in a vacuum oven and dried at 100°C for 25 hours. The dried material was ground and pressed into a sheet material with a diameter of 1 cm at a pressure of 30 MPa. The obtained material sheet was heated to 600°C at a heating rate of 2°C / min in a hydrogen-argon mixed gas, kept at this temperature for 12 hours, and naturally cooled to room temperature to obtain Na4Fe2O3 synergistically regulated by in-situ carbon-coated Fe vacancies and high entropy doping. 2.6 □ 0.1 (Ni,Co,Mn,Cu,Mg) 0.06 (PO4)2P2O7 material.

[0103] Example 4: Preparation of Na4Fe synergistically regulated by Fe vacancy and high entropy doping 2.7 □ 0.1 (Ni,Co,Mn,Cu,Mg) 0.04 (PO4)2P2O7 sodium ion battery positive electrode material (x=0.1;y=0.2)

[0104] This embodiment adopts sol-gel method to prepare Na4Fe 2.7 □ 0.1 (Ni,Co,Mn,Cu,Mg) 0.04 The preparation method of (PO4)2P2O7 positive electrode material comprises the following steps:

[0105] (1) 1 g polyvinylpyrrolidone (PVP) and 4.7 g citric acid (C6H8O7) were dissolved in deionized water (concentrations were 14.286 mg / ml and 67.143 mg / ml, respectively), and ultrasonically treated for 30 min. Then, 13.5 mmol ferric nitrate nonahydrate (Fe(NO3)3·9H2O), 0.2 mmol nickel acetate tetrahydrate (NiC4H6O4·4H2O), 0.2 mmol cobalt acetate tetrahydrate (CoC4H6O4·4H2O), and 0.2 mmol tetrahydrate were added. Hydrated manganese acetate (MnC4H6O4·4H2O), 0.2mmol copper acetate monohydrate (C4H6CuO4·H2O), and 0.2mmol magnesium acetate tetrahydrate (C4H6MgO4·4H2O) were added, heated and stirred at 80°C and 400rpm for 5h, and then 20mmol sodium dihydrogen phosphate dihydrate (NaH2PO4) was added, heated and stirred at 80°C and 500rpm for 3h, and then heated and evaporated at 90°C and 500rpm to obtain a yellow gel precursor.

[0106] (2) The precursor obtained in step (1) was placed in a vacuum oven and dried at 100°C for 25 hours. The dried material was ground and pressed into a sheet material with a diameter of 1 cm at a pressure of 30 MPa. The obtained material sheet was heated to 600°C at a heating rate of 2°C / min in a hydrogen-argon mixed gas, kept at this temperature for 12 hours, and naturally cooled to room temperature to obtain Na4Fe2O3 synergistically regulated by in-situ carbon-coated Fe vacancies and high entropy doping. 2.7 □ 0.1 (Ni,Co,Mn,Cu,Mg) 0.04 (PO4)2P2O7 material.

[0107] Figure 1 and Figure 2 The macroscopic SEM image and the local magnified SEM image of the sodium ion battery positive electrode material prepared in Example 1 of the present invention are shown. It can be seen that the material prepared in Example 1 has a distinct microspherical morphology, with uniform overall particle size and a microspherical diameter of 300-400nm. At the same time, the interwoven carbon matrix network is clearly observed in the local magnified SEM image, which greatly shortens the Na + Diffusion path, increasing the Na + The diffusion rate is also effectively improved, while also effectively improving the conductivity of the material.

[0108] Figure 3 and Figure 4The macroscopic SEM image and the local magnified SEM image of the sodium ion battery cathode material prepared in comparative example 0 of the present invention are shown. It can be seen that when the carbon source concentration is reduced, especially when the content of polyvinyl pyrrolidone is reduced, the prepared sodium ion cathode material presents irregular nanoparticles, the agglomeration phenomenon is more obvious, the diameter of the particles is relatively large, between 500-1000nm, and no microsphere morphology is observed, highlighting the importance of carbon source concentration for morphology regulation.

[0109] Figure 5 and Figure 6 The XRD full spectrum and local amplified spectrum of the sodium ion battery positive electrode materials prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 of the present invention. It can be seen that the materials prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 all have a high degree of crystallinity, and their diffraction peaks can correspond well to the Na4Fe3(PO4)2P2O7 substance, confirming the effectiveness of the preparation method and design scheme. It can be seen that the diffraction spectrum of the material prepared in Comparative Example 1 shows obvious NaFePO4 and Na2FeP2O7 impurity peaks. After the regulation of Fe vacancy alone, the impurity peak of the material prepared in Comparative Example 2 is significantly weakened, but still obvious; similarly, after the high entropy doping modification alone, the material prepared in Comparative Example 3 can also be observed to have a weak impurity peak; in particular, after the coordinated regulation of high entropy doping and Fe vacancy, no impurity peaks were detected in the material prepared in Example 1, and it has a good Na4Fe3(PO4)2P2O7 pure phase structure.

[0110] Example 5: Assembling button-type sodium ion batteries

[0111] The active material, Super P and polyvinylidene fluoride (PVDF) were ground evenly in a molar ratio of 7:2:1, and then an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added for further wet grinding. After grinding and dispersion, the slurry was evenly coated on aluminum foil, dried in a vacuum oven at 80°C for 12 hours, and cut into positive electrode sheets. Among them, the active materials were Na4Fe3(PO4)2P2O7 prepared in Comparative Example 1, Na4Fe 2.9 □ 0.1 (PO4)2P2O7, Na4Fe prepared in Comparative Example 3 2.7 (Ni, Co, Mn, Cu, Zn, Mg) 0.05 (PO4)2P2O7, Na4Fe prepared in Example 1 2.6 □ 0.1 (Ni, Co, Mn, Cu, Zn, Mg) 0.05 (PO4)2P2O7; Super P is a conductive additive, polyvinylidene fluoride (PVDF) is a binder, and aluminum foil is a current collector.

[0112] In a glove box filled with argon, the concentration of H2O and O2 was less than 0.1ppm. A metal sodium sheet was used as the negative electrode, 1M NaClO4 was dissolved in ethylene carbonate (EC) / diethyl carbonate (DEC) and 5% fluoroethylene carbonate (FEC) solution as the electrolyte, and a glass fiber membrane was used as the separator of the half-cell to assemble a CR2025 button cell. The constant current charge and discharge mode was used for testing, with a charge cutoff voltage of 4.25V and a discharge cutoff voltage of 1.75V. The test was performed at 100mA g -1 carried out at a current density of .

[0113] Figure 7 The sodium ion battery positive electrode materials prepared in Comparative Examples 1, 2, 3 and Example 1 of the present invention are 10 mA g -1 Initial charge and discharge curves under current density; among them, the material prepared in Example 1 shows a significant platform capacity improvement due to the improvement of phase purity and the synergistic effect of multiple cations, and the initial discharge capacity can reach 129 mAhg -1 (The specific capacity is calculated based on the active substance of the positive electrode material), which is significantly better than the materials prepared in Comparative Examples 1, 2 and 3.

[0114] Figure 8 The figure is a rate performance diagram of the sodium ion battery positive electrode material prepared in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 of the present invention; it can be seen that due to the flexible local environment given to the material by Fe vacancies and high entropy doping, the tolerance and structural stability of the material are enhanced, and it can better adapt to large current charge and discharge. The material prepared in Example 1 shows excellent rate performance. At 10Ag -1 Even at high current density, it still has a capacity of more than 60 mAh g -1 The specific capacity, when the current returns to 1A -1 and 0.05Ag -1 In contrast, the materials prepared in Comparative Examples 1, 2 and 3 still exhibit low capacity and poor high current tolerance due to the presence of the impurity phase.

[0115] Fig. 9 and Fig.10 The sodium ion battery positive electrode material prepared in Example 1 and Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present invention is 5Ag -1 Long cycle electrochemical performance diagram under current density; Thanks to the coordinated regulation of high entropy doping and Fe vacancies, the material prepared in Example 1 not only has high capacity, but also shows good long cycle stability, which can be used at 5Ag -1The high current density can be stably cycled for more than 6000 times, and the capacity retention rate is as high as 88.8%. After 15000 cycles, it can still maintain about 57mAh g -1 The reversible capacity of the electrode was 74.2% (capacity retention rate was 74.2%). In contrast, Comparative Examples 1, 2 and 3 were unable to withstand large current densities, and exhibited rapid capacity decay and electrode failure.

[0116] Fig.11 The in-situ XRD patterns of the positive electrode material for sodium ion batteries prepared in Example 1 of the present invention during the initial two cycles of charge and discharge correspond to the following: Example 1 undergoes a highly reversible solid solution-two-phase structure evolution process during the entire charge and discharge process, and the lattice parameters undergo a reversible change as the charge and discharge proceeds. + The reversible extraction / embedding in the material, the maximum volume change during the entire charge and discharge process is only 3.8%, and all lattice parameters can be restored to their initial state after the test. This is due to the rational design of Fe vacancies and high entropy doping schemes. 2+ Has good chemical compatibility.

[0117] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Therefore, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection of the technical solution of the present invention.

Claims

1. A sodium iron phosphate pyrophosphate positive electrode material, characterized in that: Its chemical formula is Na4Fe 3-x-y □ x HE y (PO4)2P2O7; wherein: □ is an Fe vacancy; HE is a doping element, including at least 5 of Ni, Mg, Co, Mn, Cu, Zn, Cd, Al, and Cr, and each doping element is equimolar; 0.08 <x≤0.1,0.2≤y≤0.3。 2. The sodium iron phosphate pyrophosphate positive electrode material according to claim 1, characterized in that The surface of the positive electrode material is coated with a carbon layer, wherein the carbon content accounts for 5-12wt% of the positive electrode material.

3. A method for preparing the sodium iron phosphate pyrophosphate positive electrode material according to claim 1 or 2, characterized in that: The steps include: Step S1, dissolving carbon source A and carbon source B in water, and performing ultrasonic treatment to obtain a carbon source solution; Step S2, adding the iron source and the metal doping element source into the solution of step S1 according to the stoichiometric ratio, heating and stirring; Step S3, adding the sodium source and the phosphorus source into the solution of step S2 according to the stoichiometric ratio, heating and stirring, and then evaporating to obtain a gel; Step S4, drying the gel of step S3, grinding it into powder, and then tableting it to obtain a sheet-like precursor; Step S5, calcining the sheet precursor obtained in step S4 under an inert atmosphere, and then cooling and grinding to obtain the sodium iron phosphate pyrophosphate positive electrode material.

4. The preparation method according to claim 3, characterized in that: S1 The carbon source A is one or more of polyvinyl alcohol, polyethylene glycol, polyvinyl pyrrolidone, sodium alginate, and polyacrylamide; the carbon source B is one or more of sucrose, glucose, citric acid, ascorbic acid, oxalic acid, and oxalic acid.

5. The preparation method according to claim 4, characterized in that: The concentration of the carbon source A in the carbon source solution is controlled at 12-18 mg / mL, and the concentration of the carbon source B in the carbon source solution is controlled at 65-75 mg / mL.

6. The preparation method according to claim 4 or 5, characterized in that: The carbon source A and the carbon source B are polyvinyl pyrrolidone and citric acid respectively.

7. The preparation method according to claim 4 or 5, characterized in that: The heating and stirring temperature in S2 and S3 is 60-90°C; the tableting pressure in S4 is 20-40MPa.

8. The preparation method according to claim 4 or 5, characterized in that: S5: The calcination temperature is 550-650°C, and the holding time is 8-12h.

9. A positive electrode plate for a sodium ion battery, characterized in that: It comprises the sodium iron phosphate pyrophosphate positive electrode material according to claim 1 or 2, or the sodium iron phosphate pyrophosphate positive electrode material prepared by the method according to any one of claims 3 to 8.

10. A sodium ion battery, characterized in that: It includes the sodium ion battery positive electrode plate as described in claim 9.

Citation Information

Patent Citations

  • High-entropy ferric sodium pyrophosphate sodium ion battery positive electrode material and preparation method thereof

    CN116404154A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN117239120A

  • Medium-entropy ferric sodium pyrophosphate composite material and preparation method thereof

    CN118458731A

  • Modified ferric sodium pyrophosphate positive electrode material and preparation method thereof, positive electrode plate and sodium ion battery

    CN118588913A

  • Iron-deficient manganese-doped sodium battery positive electrode material as well as preparation method and application thereof

    CN118610454A

Cited By

  • Tungsten-doped composite positive electrode material, positive electrode plate, sodium ion battery and electric equipment

    CN120998985A